Uncovering Sophie’s Narcissistic Behavior in Soman Chainani’s The School for Good and Evil Through Psychoanalysis - Larasati, Niken; Kurnia, Nandy Intan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study aims to identify Sophie's narcissistic behavior and to analyze its effects on her personality in Soman Chainani’s The School for Good and Evil (2013). This research applies Sigmund Freud’s psychoanalysis theory and Campbell & Crist’s narcissism theory to analyze the character's narcissistic behavior and its effects. This research used the qualitative method. The primary data source is Soman Chainani’s The School for Good and Evil published in 2013 by HarperCollins. In collecting the data, the writers read the novel, take notes on the important details, organize the data, and analyze the data that has been sorted using Sigmund Freud's psychoanalysis theory and Campbell & Crist's narcissism theory. The results of this study reveal that there are 24 data related to Sophie’s imbalanced personality and another 24 data about the effects of her narcissistic behavior. As shown in the data, Sophie is dominated by her id, which leads her to have narcissistic traits such as self-importance, antagonism, and a sense of entitlement. The effects of her narcissism are overconfidence, grandiosity, infidelity, aggression, mistrust, and emotional fragility. Sophie’s narcissism not only damages her relationship but also hinders her emotional and mental development. This study enables the readers to gain a deeper understanding of human psychology and how narcissism manifests and affects human behavior as seen through a literary text. Moreover, through this study, the readers can also see the close relation between the study of literature and psychology since both delve into the psychological problems experienced by human beingsKeywords: Psychoanalysis, Imbalanced Personality, Narcissism, The School for Good and Evil